An App for Every Step: A psychological perspective on interoperability of Mobile Messenger Apps - René Arnold; Anna Schneider (International Telecommunications Society (ITS), 2017)
Mobile Messaging Apps (MMAs) such as WhatsApp, Facebook Messenger, LINE, Signal or Snapchat are used by many consumers next to the traditional electronic communication services (ECS) SMS texting and phone calls. While with ECS the idea of full end-to-end interoperability is one of the key features, initial research (28 qualitative interviews) conducted by us indicate that consumers use different MMAs to negotiate their social ties. In this paper, we extend this research with an analysis of the functionalities of 139 MMAs and 20 in-depth interviews focusing on how consumers use individual services to manage stages of intimacy in relationships, communicate a message's urgency, or craft social messages. We find that the technological seams between various MMAs indeed fulfil important functions as they enable consumers to mediate competence, relatedness and autonomy as defined in Deci and Ryan's Self-Determination Theory (SDT). Furthermore, the paper shows how the choice of MMA reflects different stages of relationship development. Finally, we show that consumers also rely on technological seams between MMAs to feel autonomous and competent in their social interactions as the choice of MMA and functionality according to the specificities of the situation adheres to a finely grained social code. For policy makers and regulators, our results indicate that imposing interoperability obligations on MMAs is likely to reduce consumers' well-being given the importance of technological seams to enact self-determination.
Keywords: 330